2019
DOI: 10.1093/jmcb/mjz025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic edge-based biomarker non-invasively predicts hepatocellular carcinoma with hepatitis B virus infection for individual patients based on blood testing

Abstract: Hepatitis B virus (HBV)-induced hepatocellular carcinoma (HCC) is a major cause of cancer-related deaths in Asia and Africa. Developing effective and non-invasive biomarkers of HCC for individual patients remains an urgent task for early diagnosis and convenient monitoring. Analyzing the transcriptomic profiles of peripheral blood mononuclear cells from both healthy donors and patients with chronic HBV infection in different states (i.e. HBV carrier, chronic hepatitis B, cirrhosis, and HCC), we identified a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Progression of both TCM syndromes and complex diseases usually have nonlinear transitions [33, 35, 37]. Such a transition plays key roles in biological processes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Progression of both TCM syndromes and complex diseases usually have nonlinear transitions [33, 35, 37]. Such a transition plays key roles in biological processes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we introduced a mathematical model, i.e., the DNB method to identify the predictive biomarkers and understand the molecular mechanisms of TCM syndrome dynamic change. The DNB method has been applied successfully to studies in multiple fields (e.g., disease diagnosis and prognosis, therapeutic response, cell differentiation) [35, 3840].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al ( 28 ) identified 615 differentially hydroxymethylated regions from ANHC tissues compared to adjacent normal tissues, which were significantly enriched in gene ontology functions, and they found that some hydroxymethylated genes were involved in ANHC development. Lu et al ( 32 ) found that a panel based on four candidate genes (COL5A1, HLA-DQB1, MMP2, and CDK4) was valuable for the diagnosis of ANHC patients [with an area under the receiver operating characteristic curve (AUROC) of 0.768], and Zheng et al ( 33 ) also found that a blood-based 22-gene signature was valuable for ANHC screening (AUROC of 0.93, sensitivity of 91.3%, specificity of 83.2%). Circulating cell-free DNA (cfDNA), microRNAs, and circular RNAs are easily detected genetic biomarkers that are valuable for the diagnosis of HCC, including ANHC.…”
Section: Blood Biomarkers For Anhc Diagnosismentioning
confidence: 99%
“…Therefore, the currently available predictive signatures unavoidably tend to have limited mechanism explanatory power, which has become a common concern in precision medicine ( Robinson et al., 2013 ). There is a general consensus among both clinicians and biologists about the need for signatures with mechanistic interpretability as well as high predictive accuracy for cancer precision medicine ( Robinson et al., 2013 ; Topalian et al., 2016 ; Lu et al., 2019 ). It could also be expected that taking mechanistic interpretation into consideration would further enhance the predictive accuracy and robustness of signatures in clinical application ( Robinson et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%